CLINICAL AND IMMUNOLOGICAL EFFICIENCY OF THE INTERFERON SYNTHESIS INDUCTOR AMONG CHILDREN, SUFFERING FROM THE ACUTE RESPIRATORY INFECTIONS WITH THE ALLERGIC PATHOLOGY - V.A. Bulgakova; T.B. Sentsova; I.I. Balabolkin; N.V. Bashilova; I.V. Zubkova; E.L. Korol'kova; T.N. Korotkova (Педиатрическая фармакология)
This work presents research findings of the tiloron interferon synthesis application among children, suffering from the allergy and acute respiratory viral infections, witnessing its efficiency and safety. The use of tiloron against the acute respiratory diseases among children with the allergy contributes to much easier run of the viral infection, prevents the exacerbation of the main disease and stimulates the generation of the endogenic interferon.Key words: children, allergic diseases, acute respiratory Viral infections, interferon, tiloron.